2023
DOI: 10.3390/parasitologia3020014
|View full text |Cite|
|
Sign up to set email alerts
|

Metazoan Marine Parasites of Costa Rica: A Review

Abstract: Many new marine parasite species are added every year. Still, in some places, mainly tropical regions, marine parasites have been little studied. An exhaustive review of the indexed publications where species of parasites are reported in the marine environments of Costa Rica was carried out. The history of research on marine parasites in this region is also reviewed. A total of 147 species of marine parasites have been reported in Costa Rica as parasites of 61 different species of hosts. Most of these parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…There was a small error in the fifth sentence of the Abstract in the original publication [1]. The authors mistakenly wrote "A total of 147 species of marine parasites have been reported in Costa Rica as parasites of 61 different species of hosts".…”
mentioning
confidence: 99%
“…There was a small error in the fifth sentence of the Abstract in the original publication [1]. The authors mistakenly wrote "A total of 147 species of marine parasites have been reported in Costa Rica as parasites of 61 different species of hosts".…”
mentioning
confidence: 99%